Management of Wrong Blood Transfusion to an RhD Negative Woman in Labor - Titze TL; Hamnvik LHD; Hauglum IM; Carlsen AET; Tjeldhorn L; Nguyen NT; Akkök ÇA (Dove Medical Press, 2023)
Thomas Larsen Titze,1 Lars Henrik Dahl Hamnvik,2 Inga Marie Hauglum,1 Anne Elisabeth Tonay Carlsen,2 Lena Tjeldhorn,3 Nhan Trung Nguyen,3 Çiğdem Akalın Akkök3 1Department of Laboratory Medicine, Vestre Viken Health Trust, Drammen, Norway; 2Department of Hematology, Vestre Viken Health Trust, Drammen, Norway; 3Department of Immunology and Transfusion Medicine, Oslo University Hospital, Oslo, NorwayCorrespondence: Çiğdem Akalın Akkök, Department of Immunology and Transfusion Medicine, Oslo University Hospital, Ullevaal, Kirkeveien 166, Oslo, N-0407, Norway, Tel +47 92 03 47 47, Fax + 47 22 11 88 50, Email cigdemakak@yahoo.noAbstract: Blood transfusion is life-saving in massive hemorrhage. Before pre-transfusion tests with ABO and RhD typing results are available, O RhD negative packed red blood cell (PRBC) units are used without cross-matching in emergency. RhD negative girls and women of child-bearing age should always receive RhD negative blood transfusions to prevent RhD-alloimmunization because anti-D-related hemolytic disease of fetus and newborn (HDFN) can result in mild to severe anemia, and in a worst-case scenario death of an RhD positive fetus and/or newborn. However, “wrong blood to wrong patient” happens unintentionally. Here we report an emergency blood transfusion with one unit of RhD positive PRBCs to an RhD negative young woman when estimated blood loss was 2500 mL during delivery and surgical removal of retained placenta. Realizing the mistake, management with high dose anti-D immunoglobulin (Ig) was initiated to remove the RhD positive red blood cells (RBCs) from the patient’s circulation. Such mitigation is recommended only for girls and women of child-bearing age. Follow-up was performed by flow cytometry until RhD positive RBCs were no longer detected. Ten months after the delivery, antibody screening was negative. However, we still do not know whether we managed to prevent RhD-alloimmunization.Keywords: anti-D antibody, anti-D immunoglobulin, alloimmunization, fetomaternal hemorrhage, pregnancy, Rhesus